Ciudadanía y educación.Una brújula para la democracia (Altre Modernità, 2016)
The virtuous relationship among education, citizenship and democracy is paramount in contemporaneity. This controversial conceptual triangle is associated to the origin of political education and to the development of national educational systems that aim at training citizens who are essential to the support and advance of democracy. Education to citizenship has been referred to in the political and educational sectors with different definitions, names and purposes, but there is no shared definition regarding its aims, theoretical applications, contents, pedagogical models and objectives.Currently, within the context of the processes of democratization in Latin America and Mexico, the concept of citizenship is being redefined and its role in the education of citizens, both old and new, is being revalued. At the same time, new educational and social actors are emerging, who, with different initiatives, tend to train more active citizens who will participate in public life, having an interested impact on it, which will go beyond participation in elections.This essay will not only reflect on what has been argued so far, but it also aims at highlighting a concept of substantive citizenship based on rights and responsibilities, which requires individuals to be educated to participate and develop the necessary competences to put their rights as human beings and citizens into practice.